EFFECTIVENESS OF PROBIOTIC AND DIGESTIVE ENZYMES IN FERMENTED DIET ON GROWTH, FAT AND CHOLESTEROL CONTENTS OF BROILER - Yaman, Dr. M Aman (Jurnal Kedokteran Hewan, 2022)
ABSTRACTThe present study aims to determine the effect of fermented diet containing probiotics and digestive enzymes with different feed levels on growth, fat and cholesterol contents of broiler chickens. Evaluating the effectiveness of probiotics (P) and digestive enzymes (DE) in fermented diet on broiler was observed by 4 treatments: P0=control (fermented diet without P and ED) EP), P1(fermented diet contained 0.5% P only)), P2 (fermented diet contained 0.5% DE only), P3 (fermented diet contained 0.5% P and 1% DE) and P4 (fermented diet contained 1% P and 0.5% DE). A hundred DOCs of broiler chickens strain CP 707 were used (unsex) and it designed by a completely randomized design with 5 treatments, 4 replications and each replication consisted of 5 DOCs. The data obtained were analyzed by means of variance and Duncan's multiple range test. The results of present study showed that broiler fed on fermented diet containing P and/or ED with different levels had a significant effect (P0.05) on final body weight, weight gain, carcass weight, fat content on thigh muscle. Broiler fed on fermented diet contained 0.5% DE only (P2) resulted in better growth and weight gain than other treatments. However, fermented diet contained probiotics and digestive enzymes had no effect on fat and cholesterol contents in breast muscle. It was concluded that the addition of digestive enzymes in fermented diet formulated by local raw materials was very effective than probiotics in increasing body weight gain, carcass weight and prevented the increase in fat and cholesterol contents both in breast and thight muscles of broiler chicken.